2022
DOI: 10.4235/agmr.22.0027
|View full text |Cite
|
Sign up to set email alerts
|

Association between Sarcopenia and Cognitive Functions in Older Individuals: A Cross-Sectional Study

Abstract: Background: Sarcopenia and cognitive disorders are frequently observed in older individuals. This study investigated the relationship between sarcopenia and cognitive function in this population.Methods: This cross-sectional study included 201 participants aged >65 years in Istanbul between July 1, 2020 and January 31, 2021. We screened all participants using the SARC-F (strength, assistance with walking, rising from a chair, climbing stairs, and falls) questionnaire to determine the risk of sarcopenia. Han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…A total of 1,870 articles were initially evaluated. Eventually, 12 articles were included in our study [1][2][3][4][5][6][7][8][9][10][11][12] . The cumulative sample size across all the included studies amounted to 3,975 participants.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 1,870 articles were initially evaluated. Eventually, 12 articles were included in our study [1][2][3][4][5][6][7][8][9][10][11][12] . The cumulative sample size across all the included studies amounted to 3,975 participants.…”
Section: Resultsmentioning
confidence: 99%
“…In a similar vein, by conducting a secondary prevention study with 200 men aged 57.3±6.3 years, the work of Lutski et al [ 34 ] showed that subjects with two or more chronic conditions had a greater probability of experiencing subjective cognitive impairment over a 20-year follow-up period. Taken together, it appears that comorbidities result in physical and functional limitations or changes in brain macrostructure and microstructure, which have a negative impact on cognitive function [ 35 , 36 ] or vice versa [ 37 , 38 ]. As a result, a prospective cohort study will be required to determine the precise direction of the relationship between comorbidities and cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, muscular strength is just as important as PA in reducing the physical- and mental-health burden of chronic disorders, such as depression [ 41 ] and cognitive decline [ 36 ]. For example, by examining data taken from the KLoSA 2006–2015 and 2014–2018, respectively, Jeong and Kim [ 42 ] and Lee et al [ 43 ] demonstrated that low handgrip strength was positively related to an elevated risk of cognitive impairment among older Korean adults.…”
Section: Discussionmentioning
confidence: 99%
“…The lowest global cognition score was linked to a type of fat called sarcopenic fat. A cross-sectional study by Yigit et al 26 ) on 201 participants aged >65 years in Istanbul reported significantly higher scores in older individuals with reduced cognitive function compared to the scores in participants with normal cognitive functions.…”
Section: Prevalence Of Sarcopenic Obesitymentioning
confidence: 98%